Nepotisme Politik Kekuasaan dan Upaya Pemecahannya - Saebani, Beni Ahmad; Mubarok, Adrian Farhan (CV Era Digital Nusantara, 2024)
Nepotism in Indonesia is a complex phenomenon and rooted in the culture of kinship and the patronage system. One of the most common patterns of nepotism in Indonesia is the appointment of officials and staff based on family or relative relationships, not on the basis of qualifications or competencies. Various strategic positions in the government are filled by family members or close relatives of political officials. Effective and strong law enforcement can dispel the practice of nepotism. Strengthening the capacity of law enforcement agencies and internal oversight mechanisms in each institution will ensure that every case of nepotism is handled seriously and transparently. Cultural change and institutional governance are important aspects in efforts to overcome nepotism. It is also important to conduct ethics education and training for all employees and public officials that includes an understanding of the negative impact of nepotism and the importance of integrity in decision-making. It is also necessary that continuous ethics training can build awareness and commitment to fair practices. Through ethics education, organizations can build a culture of integrity that rejects all forms of nepotism.Increasing transparency in the decision-making process is an important step to reduce nepotism by providing open access to information about the recruitment, promotion, and procurement process. Transparency in the administrative process can reduce the likelihood of nepotism and increase public trust.Organizations must adopt policies that encourage information disclosure and ensure that every decision taken can be held accountable. An effective complaint channel can improve the detection and handling of nepotism cases. Effective monitoring and evaluation mechanisms are needed to overcome nepotism. The use of technology will increase scrutiny of nepotism practices, as technology can increase efficiency and transparency in human resource management, reduce subjective intervention in decision-making processes and ensure that every decision is based on objective data so that at a consistent and sustainable level of implementation it will help build a fairer system and increase public trust in institutions.